Towards recognition of subsistence harms: reassessing approaches to socioeconomic forms of violence in transitional justice - Sankey, Diana (International journal of transitional justice, 2014)
Deprivations of subsistence needs, involving attacks on homes, livelihoods and basic resources, constitute a discreet and direct form of violence but remain marginalized within transitional justice. The article introduces the concept of ‘subsistence harms’ to name deprivations of the physical, mental and social needs of human subsistence, perpetrated with intent or with knowledge of the inevitable consequences of such deprivations. The concept seeks to promote more coherent and comprehensive recognition of these harms within transitional justice, as well as tighter categorization of harms related to socioeconomic concerns and a clearer understanding of the scope of transitional justice. As direct harms, subsistence harms can, and should, be comprehensively addressed by transitional justice mechanisms. Nevertheless, some realignment of thinking may be required to contest dominant concepts of violence and the limitations of the existing legal framework in order to enable the essence of these harms to be recognized.